4CPS-143 Evaluation of knowledge of patients with inflammatory bowel disease treated by the reference product concerning biosimilars: role of clinical pharmacists. (March 2019) - Coget, E; Laffont-Lozes, P; Velasco Gonzalvo, V; Huc, D; Pineton de Chambrun, G; Altwegg, R; Blanc, P; Pageaux, GP; Rosant, D; Breuker, C
Abstract : Background: Anti-TNF monoclonal antibodies such as infliximab have revolutionised the treatment of patients with inflammatory bowel disease (IBD). For a few years several biosimilars of the reference product (RP) have reached the European market and switching IBD patients from original infliximab to biosimilars is the subject of debate. Purpose: The aim of our study was to investigate IBD patients' knowledge about infliximab biosimilars and their judgement concerning switching to a biosimilar. Material and methods: We conducted a prospective observational study over a 5 month period (May to September 2018) in the outpatient clinic of the Gastroenterology Department at a tertiary referral centre. Clinical pharmacists performed a standardised interview of consecutive adult IBD patients treated with RP. The interview included general information about anti-TNF monoclonal antibodies and biosimilars, and a questionnaire on patients' acceptance of switching to a biosimilar. For each patient included, a pharmaceutical note was edited in the patient's medical record in order to inform the physician about patient knowledge and judgement. Results: A total of 64 IBD patients (46 Crohn's disease, 18 ulcerative colitis) were included in the study: 48% of males, mean age was 44±16 years. The mean duration of RP therapy was 6.5±11 years. The majority of patients (n=59, 92%) did not know anything about biosimilars. After the interview, 38% of patients (n=24) declared their acceptance of switching to a biosimilar, 23% (n=15) refused the switch and 39% (n=25) were indecisive. The main causes of refusal were the fear of a loss of efficacity in one patient, the fear of tolerance problems in three patients and both in two patients. Regarding indecisive patients, 44% (n=11) were open to considering the switch to a biosimilar after discussion with their referring physician. Conclusion: In our study we showed a significant lack of knowledge of IBD patients treated with RP concerning biosimilars. Nonetheless, after an interview with a clinical pharmacist, most of the patients had a positive perception of biosimilars and accepted the switch from original infliximab to a biosimilar. This study highlighted the need for patient education about biosimilars in order to authorise the switch of biologics and the major role of clinical pharmacists in providing this education. References and/or acknowledgements: http://www.worldgastroenterology.org/UserFiles/file/guidelines/inflammatory-bowel-disease-english-2015-update.pdf No conflict of interest.